Экотехнология водоподготовки - Слепцов, Георгий Владимирович; Слепцов, Виктор Георгиевич; Лисогор, Елена Сергеевна (Eastern-European Journal of Enterprise Technologies, 2009)
Main problems of main stages of process technology of natural water treatment are formulated, also the possibility of application of ecotechnologies is shown. Equations of chemical thermodynamics and equations of nonequilibrium chemical kinetics for the process description of water treatment are posed. Researches that were made give the possibility for main principles of water treatment’s ecotechnologies formulation.